Learning Management in Virtual Classroom: A Phenomenological Study - Sumalinog, Gino Gasang; Corales, Erwin; Goles, Charess (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2022)
This study explored the online learning management experiences of the teachers during the COVID-19 crisis. This paper used the phenomenological research design, and it employed the Interpretative Phenomenological Analysis (IPA) as its data analysis method. A semi-structured interview was used to capture the lived experiences of the ten (10) higher education teachers from the selected schools in Central Visayas in the Philippines. After an intensive and careful analysis of the transcripts, three (3) significant themes from the teachers' perspectives emerged. They were: a) the lows; b) the highs; and c) the gains from the online learning setup. The study revealed that learning management failure was due to poor grading bases since teachers were not sure whether the students were honest in answering their tasks. The informants also noticed abysmal participation and inappropriate behavior from the students. However, they highlighted that at some point, managing a classroom online was made easy because of the secured, accessible, and organized files that teachers could use in handling their classes. They have also gained some positive personal attributes, professional teaching insights, and practical financial benefits. This study could be of great help to teachers who have not embraced the use of virtual classrooms in managing students’ learning. This is a timely research topic since the pandemic has just struck.